(untitled) (UNIZIK Journal of Agricultural Economics and Extension, 2024)
This research sought to find the ‘Effects of Climate-Smart Agricultural Practices on Food Security Situation of Farmers in Nasarawa State’. A multistage sampling approach was used to select 222 farmers. Primary data were collected using a questionnaire. Data were analyzed using principal component analysis, household dietary diversity score, Poisson regression analysis and descriptive statistics. Principal component analysis grouped climate-smart agricultural practices into 5 components namely; comprehensive field management (42.0%), on-farm risk reduction (16.0%), crop/livestock management (13.0%), agroforestry (9.0%) and soil conservation practices (20.0%). A household dietary diversity score of 2.7 was obtained. Results of regression analysis showed that participation in non-agricultural activities, household size, valuable farm assets, comprehensive field management, on-farm risk reduction and crop/livestock management were significant. The absence of information (36.0%) and capital (28.8%) were the main challenges to the use of the technology. The research concludes that climate-smart agricultural practices have the potential to improve the food security situation of the farmers.